Transit Bus Operational and Maintenance Practices to Maximize Fuel Economy - World Bank (Washington, DC, 2014)
Buses are the most common form of urban transit but, in the developing world, are often seen as inefficient and polluting. It is well known that buses that are properly tuned and adjusted tend to be cleaner, safer and consume less fuel than poorly maintained buses. Fuel cost is a relatively large fraction of total cost especially when labor and bus costs are low, as in many developing countries. Hence, reducing fuel use through targeted maintenance of fuel inefficient buses can reduce significant expenditures especially in developing countries, freeing up resources for other improved city services. In addition, if city buses do not receive periodic maintenance that is adequate in quality and quantity, their emissions, both local and global, will suffer. In an effort to catalyze solutions for urban transport, the World Bank Group focused on development of a global Knowledge Product in the form of a 'Guidance Note' (GN) on bus maintenance procedures. The GN is directed towards city transit managers and their technical staff in developing countries to enhance the energy efficiency of city transit. The objective of this work effort is to prepare a Guidance Note (GN) on maintenance best practices that is a practical and useful tool to guide the implementation of a program that will enhance the fuel efficiency of buses. To address this objective, taking stock of existing good programs and approaches and interacting with relevant city fleet operators is critical.